Penerapan Problem Based Learning Berbantuan E-Magazine Untuk Meningkatkan Hasil Belajar Materi Fluida Statis - Adhan, Haryadi; Hanisa Putri, Desy; Purwanto, Andik (Navigation Physics : Journal of Physics Education, 2023)
The Problem Based Learning model  is able to stimulate students to analyze problems, provide hypotheses, search for data, process data and conclude the results of analysis of answers to problems. The purpose of this study is to determine the effect of the application of E-Magazine-assisted Problem Based Learning  on learning outcomes. And knowing the response of students to the use of  Problem Based Learning assisted by E-Magazine in learning static fluid material. This research was carried out at SMAN 7 Bengkulu City in the odd semester of 2023/2024. The research method used is pre-experimental research  using a one group pretest-posttest design. The instruments used are objective question test sheets and response questionnaire sheets. Hypothesis test with statistical analysis  of t-test paired samples test obtained significance results (1-tailed) of <.001 < 0.05. The results of student responses to the problem-based learning model (Problem Based Learning) assisted by E-Magazine are 90% with very good criteria.  Based on this research, it can be concluded that  Problem Based Learning assisted by E-Magazine has an influence on student learning outcomes in static fluid material.